Improvement of microstructure of bovine hydroxyapatite with yttria - (:unkn) unknown (Trans Tech Publications Ltd, 2007)
Composites of calcinated bovine bone derived hydroxyapatite (HA) with 0.5 and 1 wt% Y2O3 were prepared by sintering. Money and time saving feature the production of HA from natural sources. In this study, results of scanning electron microscopy (SEM) and X-ray diffraction analysis aimed to interpret the results of measurements of densification, microhardness, and compression strength of the produced composites. The best mechanical properties were achieved after sintering at 1200°C for compressive strength and 1300°C for microhardness. The results are in a fair agreement with densification measurements and microstructure analysis.
Keywords: Hydroxyapatite; Mechanical properties; Microstructure; Sintering; Yttria